Analysis of the Efficacy and Safety of Avatrombopag Combined With MSCs for the Treatment of Thrombocytopenia After Allogeneic Hematopoietic Stem Cell Transplantation - Zhu, Lidan; Liu, Jia; Kong, Peiyan; Gao, Shichun; Wang, Lu; Liu, Huanfeng; Zhang, Cheng; Gao, Li; Feng, Yimei; Chen, Ting; Gao, Lei; Zhang, Xi (Frontiers in Immunology, 2022)
Platelet graft failure (PGF) is a frequent and serious complication after Allogeneic hematopoietic stem cell transplantation (allo-HSCT) and lacks effective treatment strategies, which could affect the prognosis of patients and even cause death. The exact underlying mechanism of PGF remains unclear, and lacks standard treatment. Here, we conduct a retrospective study to the efficacy and safety of avatrombopag combined with mesenchymal stem cells (MSCs) in 16 patients with thrombocytopenia after allo-HSCT. Patients were administered the following treatment regimen: 20 mg/d avatrombopag; if the PLT count was less than 50×10^9/L for at least 2 weeks, the dose was increased to 40 mg/d; if the PLT count was 200-400×10^9/L, the dose was reduced; and if the PLT count was greater than 400×10^9/L, avatrombopag was terminated. Umbilical cord MSCs (1×10^6/kg) infusion was performed every week for 4-6 weeks. Among the 16 patients, 13 patients (81.3%) had a complete response (CR), 2 patients (12.5%) had a partial response (PR), and 1 patient (6.3%) had no response (NR). The median time to obtain CR was 32 (7-426) days after treatment with avatrombopag combined with umbilical cord MSCs. The time to reach 20×10^9/L≤ PLT <50×10^9/L in the 2 patients with PR was 52 and 230 days after treatment, respectively. One patient had a severe pulmonary infection and died of cytomegalovirus pneumonia. Overall, our results indicated that combination of avatrombopag with MSCs can promote platelet recovery after transplantation, thereby improving the survival rate of patients and improving the quality of life of patients after transplantation, and providing a new method and strategy for the treatment of thrombocytopenia after allo-HSCT.